Komunikasi Dalam Manajemen Pada Implementasi Kurikulum Merdeka - Dianto, Aris; Kusen; Sumarto; Valentine, Femalia (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
Curriculum change is one of the efforts aimed at improving the quality of education in Indonesia. This study examines communication in educational management and explores the implications of implementing the "Merdeka" curriculum. The purpose of this research is to describe the role of communication in the implications of implementing the "Merdeka" curriculum. This is a qualitative study using a literature review method. Literature data is collected, analyzed, and examined to obtain research results. The findings of this study indicate that the function of communication plays a role in several implications of the implementation of the "Merdeka" curriculum, namely, (1) communication as planning and goal achievement in the aspect of curriculum structure changes; (2) communication as a source of educational information and communication as a controller and coordinator in the aspect of the learning process, and; (3) communication as a source of educational information in the aspect of assessment.